The Protective Effect of Beraprost Sodium on Diabetic Cardiomyopathy through the Inhibition of the p38 MAPK Signaling Pathway in High-Fat-Induced SD Rats - Jie Li; Li Peng; Hong Du; Yangtian Wang; Bin Lu; Yixin Xu; Xiaozhen Ye; Jiaqing Shao (International Journal of Endocrinology)
Objective. To investigate the effect of beraprost sodium (BPS) on diabetic cardiomyopathy and the underlying mechanism. Methods. A total of 40 Sprague Dawley rats were randomly divided into the normal control group (N=10) and the model group (N=30). The model group was fed a high-fat diet followed by a one-time dose of streptozotocin (STZ) to establish the diabetes mellitus model. After that, rats were randomly divided into two groups with or without BPS intervention. After 8 weeks, we explored the role of the p38 MAPK signaling pathway in inflammation, oxidative stress, cardiac morphology, and myocardial apoptosis. Results. Compared with control, the ratio of heart-weight to body-weight and the serum levels of SOD and GSH in the BPS group significantly increased, the expression of p38 MAPK, the serum levels of MDA, TGF-β1, TNF-α, HIF-1α, MMP-9, caspase-3, BNP, ANP, and heart Bax expression significantly decreased, and heart Bcl-2 expression significantly increased. H&E staining in diabetic rats showed the cardiac muscle fibers derangement, the widening gap, the pyknotic and fragmented nuclei, and more apoptosis. Conclusions. BPS effectively showed protective effects on diabetic myocardial cells, possibly through the inhibition of p38 MAPK signaling pathway.